Risk of Hip Fracture Associated with Hepatitis C Virus Infection and Hepatitis C/HIV Coinfection - Re, Vincent Lo (2012)
Hepatitis C virus (HCV) infection has been associated with reduced bone mineral density, but its association with fracture rates is unknown, particularly in the setting of human immunodeficiency virus (HIV) coinfection. Our objectives were to determine whether persons with HCV infection alone are at increased risk for hip fracture compared to uninfected individuals and to examine if the risk of hip fracture is higher among HCV/HIV-coinfected persons compared to those with HCV alone, those with HIV alone, and those uninfected with either virus. We conducted a cohort study in 36,950 HCV/HIV-coinfected, 276,901HCV-monoinfected, 95,827 HIV-monoinfected, and 3,110,904 HCV/HIV-uninfected persons within the U.S. Medicaid populations of California, Florida, New York, Ohio, and Pennsylvania (1999–2005). Incidence rates of hip fracture were lowest among uninfected persons (1.29 events/1000 person-years), increased with the presence of either HIV infection (1.95 events/1000 person-years) or HCV infection (2.69 events/1000 person-years), and were highest among HCV/HIV-coinfected individuals (3.06 events/1000 person-years). HCV/HIV coinfection was associated with an increased relative hazard (adjusted hazard ratio [95% confidence interval]) of hip fracture compared to HCV-monoinfected (1.38 [1.25–1.53]), HIV-monoinfected (females: 1.76 [1.44–2.16]; males: 1.36 [1.20–1.55]), and uninfected persons (females: 2.65 [2.21–3.17]; males: 2.20 [1.97–2.47]). HCV monoinfection was associated with an increased risk of hip fracture compared to uninfected individuals, and the relative increase was highest in the youngest age groups (females, 18–39 years: 3.56 [2.93–4.32]; males, 18–39 years: 2.40 [2.02–2.84]). CONCLUSION: Among Medicaid enrollees, HCV/HIV coinfection was associated with increased rates of hip fracture compared to HCV-monoinfected, HIV-monoinfected, and HCV/HIV-uninfected persons. HCV-monoinfected patients had an increased risk of hip fracture compared to uninfected individuals.